2019
DOI: 10.1080/03008207.2019.1653289
|View full text |Cite
|
Sign up to set email alerts
|

Blocking substance P signaling reduces musculotendinous and dermal fibrosis and sensorimotor declines in a rat model of overuse injury

Abstract: Purpose/Aim: Substance P-NK-1R signaling has been implicated in fibrotic tendinopathies and myositis. Blocking this signaling with a neurokinin 1 receptor antagonist (NK1RA) has been proposed as a therapeutic target for their treatment. Materials and Methods: Using a rodent model of overuse injury, we pharmacologically blocked Substance P using a specific NK1RA with the hopes of reducing forelimb tendon, muscle and dermal fibrogenic changes and associated pain-related behaviors. Young adult rats learned to pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…8 a) is a neuropathic pain behavior typically linked to median nerve pathology [ 11 , 73 , 74 ]. In our model, cold temperature hypersensitivity is associated with median nerve inflammation and fibrosis [ 10 , 11 , 75 ], and can be prevented or reduced pharmacologically by blocking signaling of CTGF/CCN2 (connective tissue growth factor/cell communication network factor 2) using a specific monoclonal antibody called FG-3019 or pamreluvmab [ 11 , 40 ], by blocking substance P signaling using a neurokinin 1 receptor antagonist [ 75 ], and here by the early and continued administration of a manual therapy for 12 weeks in TASK-Tx rats. Although the literature is mixed on this topic perhaps due to differences in treatment type, time of administration, assessment tools, and high variability in diagnoses [ 76 , 77 ], several clinical studies have shown that pain symptoms associated with median neuropathies can improve after massage/manual therapies [ 76 , 78 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 a) is a neuropathic pain behavior typically linked to median nerve pathology [ 11 , 73 , 74 ]. In our model, cold temperature hypersensitivity is associated with median nerve inflammation and fibrosis [ 10 , 11 , 75 ], and can be prevented or reduced pharmacologically by blocking signaling of CTGF/CCN2 (connective tissue growth factor/cell communication network factor 2) using a specific monoclonal antibody called FG-3019 or pamreluvmab [ 11 , 40 ], by blocking substance P signaling using a neurokinin 1 receptor antagonist [ 75 ], and here by the early and continued administration of a manual therapy for 12 weeks in TASK-Tx rats. Although the literature is mixed on this topic perhaps due to differences in treatment type, time of administration, assessment tools, and high variability in diagnoses [ 76 , 77 ], several clinical studies have shown that pain symptoms associated with median neuropathies can improve after massage/manual therapies [ 76 , 78 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…With knowledge from previous research that SP is involved in chronic inflammation, neuropathic pain, and tendinopathy and is critical for cell proliferation, we aimed to show the varying effects of SP depending on its duration of exposure on the tendons in vitro and in vivo [ 25 , 26 , 27 ]. Barbe et al reported that SP plays a crucial role in the fibrogenic responses and proposed blocking SP-neurokinin-1 receptor signaling with a neurokinin 1 receptor antagonist as a therapeutic target for musculotendinous and dermal fibrosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it was found that the treatment reduced the fibrogenic responses in the tendon. It was also found that motor decline, mechanical hypersensitivity, and cold temperature aversion underwent improvements [ 42 ]. Nevertheless, it is still unclear and to be confirmed whether the NK1R antagonist can reduce or improve changes in tendinopathy occurring in various anatomical sites in humans.…”
Section: Tendinopathymentioning
confidence: 99%